CORRELATION BETWEEN ALDEHYDE DEHYDROGENASE 1A1 LEVEL AND BONE METASTASIS IN PROSTATE CANCER - Moeljono, Abraham; Danarto, Danarto (Indonesian Journal of Urology, 2015)
Objective: To determine the association between Aldehyde Dehydrogenase 1A1 (ALDH1) expression and metastasis in prostate cancer. Material & methods: This study was a prospectivestudy in 45 patients diagnosed with prostate cancer in Sardjito General hospital. Patient characteristics and patient clinical data were recorded. Paraffin blocks of 45 patient surgery results were performed with immunohistochemical staining with monoclonal antibody of anti ALDH1A1 (EP1933Y, Biocare, dilution 1: 200). ALDH1 expression differences between prostate cancer without metastases and prostate cancer with metastasis was compared and analyzed with Chi-square. Results: This study involved 45 prostate cancer patients with median of age of 74 years. A high Gleason scores was found in 25 (55.6%) patients with prostate cancer and 24 (53.3%) patients had metastasis to the bone. The high expression of ALDH1 was found in 30 (66.7%) patients. The incidence of bone metastasis in patients with prostate cancer was associated with high levels of ALDH1 (p < 0.001, OR, 95% CI 17.88 (3.28-97.83) and was not associated with Gleason score (p = 0.316). Conclusion: Prostate cancer cells with high ALDH1A1 level increased the risk of the incidence of bone metastasis. ALDH1A1 level in prostate cancer cells can be considered as a predictor factor of the bone metastasis in prostate cancer.